DIGITAL TOOLS IN TEACHING VISUAL ARTS FOR GRADES 5–7 IN GENERAL SECONDARY SCHOOLS: PEDAGOGICAL STRATEGIES - Xamidova Dildora Muhiddin qizi (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
Annotation: This article discusses the application of digital tools in teaching visual arts to students in grades 5–7 in general secondary schools. It highlights innovative pedagogical strategies, including interactive lessons, multimedia resources, and project-based learning, designed to enhance students’ creativity, technical skills, and visual literacy. The study emphasizes the effectiveness of digital technologies in fostering engagement, collaboration, and individual learning progress in art education.